Digital Workflow of Customized Implants and Fabrication Using Additive Manufacturing Technology - Khaja Moiduddin (Current Innovations in Chemical and Materials Sciences Vol. 3, 2023)
Additive Manufacturing (AM) is gradually starting to attract interest in medical application due to its customization, cost effective production and faster delivery. The introduction of AM to a digital workflow, decreases the lead time by speeding the work flow of patient diagnostic information between the surgeon and the laboratory. The objective of this study is to illustrate the route to digitize the customized implants consisting of image acquisition, processing, implant design, fitting rehearsal and fabrication using fused deposition modeling (FDM) and electron beam melting (EBM) methodologies. AM of metal and plastic materials offers high levels of functional integration for industrial applications and design-driven integrated production solutions. The use of AM in medicine is growing quickly and is predicted to completely transform the health care industry. Given the inherent uniqueness of human anatomy, additive manufacturing (AM) plays a crucial role in the production of patient-specific implants. By using AM technology, these implants are designed to precisely match the individual’s bone shapes, ensuring a flawless fit. The use of additive manufacturing (AM) enables the creation of intricate lattice structures with complicated geometries, which in turn greatly enhances the pace of healing subsequent to the implantation into the human body. Over the course of the last decade, a significant proportion of implants have been conventionally manufactured by processes such as casting, forging, machining, and powder metallurgy. The conventional implants need manual manipulation prior to surgery, including a trial and error process to get a customized fit with the patient’s bone form. Any discrepancies in this process might lead to the failure of the implant. The customized implant produced using AM technique from the patients computed tomography or Magnetic resonance imaging (CT/MRI) scans can drastically reduce the implant failure and the number of revisions thus minimizing the psychological stress and pain to the patient.